(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to assess the prevalence of post-stroke depression (PSD) and identify associated factors among stroke survivors in Vietnam. Methods: A cross-sectional study was conducted at four hospitals in Hanoi from December 2023 to March 2025. A total of 185 stroke survivors were recruited using convenience sampling. Data were collected using a self-administered questionnaire, including the PHQ-9, PSQI, and Barthel Index. Statistical analysis was performed using SPSS 22.0. Results: PSD was present in 68.1% of participants (PHQ-9 > 4). No significant associations were found between depression and demographic or clinical variables. However, poor sleep quality (p = 0.00), higher levels of dependency (p = 0.01), and slower functional recovery (p = 0.03) were significantly associated with PSD. Conclusion: Post-stroke depression is common among Vietnamese stroke survivors. Poor sleep, high dependence, and delayed rehabilitation progress are key factors associated with PSD. Early detection and integrated psychological support should be prioritized in post-stroke care.